Abomasal Impaction in a Goat - Surgical Approach - Barbosa Silva, José Ricardo [UNESP]; de Moura Alonso, Juliana [UNESP]; Abreu Mendonça, Ana Paula [UNESP]; Mendes, Leticia Hirata [UNESP]; Hussni, Carlos Alberto [UNESP]; Garcia Alves, Ana Liz [UNESP]; Watanabe, Marcos Jun [UNESP]; Rodrigues, Celso Antonio [UNESP] (Universidade Federal do Rio Grande do Sul, 2023)
Background: The abomasum is glandular and has a bagpipe shape, with a capacity of 1 to 2 liters. It has a very acidic content with a pH ranging from 1.5 to 3, and although disturbances in this organ are uncommon in small ruminants, abomasal emptying defect is probably the most common abomasal problem in goats. The etiology of an abomasal emptying defect is unknown, however, abomasal impaction is the main cause of this condition. Since this disorder is associated with poor prognosis and information in goats is scarce, the aim of this report is to describe the success of abomasotomy as a treatment for abomasal impaction in goats, as well as to describe the clinical and laboratory aspects of this disease. Case: A 8-month-old male Anglo-Nubian goat, weighing 33 kg, presented with apathy and decreased appetite for 4 days due to digestive disorder. According to history, the diet consisted of crushed hay ad libitum and 300 g of ration bran. Clinical findings were apathy, pale mucous membranes, ruminal hypomotility, decreased fecal output, tense abdomen with distention of the ventral quadrants and loss of rumen stratification. The increase in chloride ion concentration (67 mEq/L) observed in the ruminal fluid analysis was indicative of abomasal-ruminal reflux, compatible with metabolic acidosis, as well as the dense hyperechogenic content in the ventral field of the left and right abdomen corresponding to the location of the entire abomasum on transabdominal ultrasound. Thus, clinical, laboratory and ultrasound findings were indicative of impaction of the abomasum, and the goat underwent exploratory laparotomy through the left flank, which revealed a distended and compacted abomasum. Differently from reports in the literature, due to severe distension of the abomasum, abomasotomy through the right flank was chosen to reverse the condition, followed by constant monitoring and supportive therapy with antimicrobial and analgesic medication. The goat defecated normally on the second postoperative day, however, on auscultation, there was persistence of abomasal emptying failure, suggesting a situation of posterior functional stenosis. With the suspicion of type III vagal indigestion, the atropine test, along with radiographic examination of the chest and abdomen were performed, and did not reveal any changes. In order to restore abomasal motility, intensive therapy with prokinetic drugs (bromopride, metoclopramide and promethazine) was associated, and on the fifth day the animal returned to normal appetite, abomasal motility and fecal production. The goat was discharged after 14 days of intensive care with recommendations to provide good quality food and water. Discussion: Abomasal impaction is rarely reported in goats, commonly resulting in animal death before or even a few days after surgical correction. The diagnosis of abomasal impaction was based on clinical, laboratory and ultrasound findings, and should be differentiated from other diseases that progress with abdominal distention and gradual weight loss, such as functional stenosis; duodenal obstruction; vagal nerve disorder; abomasite; generalized peritonitis, and granuloma associated with Actinobacillus lignieresii. Surgical correction by right paralombar access associated with visceral emptying and supportive therapy of impaction abomasal was performed and considered successful, without relapses and secondary complications long-term.
Keywords: abomasal disorders; abomasotomy; hoflund syndrome; small ruminant